Development of MolBEST (STEM-Based Mobile Learning) on Elasticity Materials - Niluh Dewanty Anindya Warsa; Abd. Kholiq (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
Several researchers have researched mobile learning development, but it is different from MolBEST (STEM-Based Mobile Learning). This is because MolBEST developed has features that can train scientific literacy and 21st-century skills that integrate science, technology, engineering, and mathematics. This research aims to develop a mobile learning form of MolBEST and to describe the feasibility (validity, effectiveness, and practicality) of mobile learning. This study uses a developmental design of the Hannafin & Peck model using material and media validation instruments, pretest posttest, and assisted learning implementation observation sheets MolBEST. Based on the analysis of research data, the percentage of MolBEST on the elasticity material from two expert lecturers is classified as very valid with a percentage of 95%. As for the effectiveness, there was an increase in students' scientific literacy skills with an N-gain of 0.64 having moderate criteria and 91% of student responses having very good criteria. The level of practicality in learning is 84% and is categorized as very good. Referring to the results of the validity, effectiveness, and practicality of using MolBEST in learning, it can be concluded that MolBEST is suitable for physics learning. Mobile learning helps increase motivation to learn, understand the material and learn independently easily anywhere and anytime.